ANALISIS BISNIS STRATEGI PADA BRAND BREAKMACKS DALAM BISNIS BREAKFAST FOOD - Anggita Nur Fatimah; Agus Rahayu; Puspo Dewi Dirgantari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research focuses on BreakMacks Brand Business Plan Analysis in the Beakfast Food Business. The research method used is the study of literature, data collection methods and methods of analysis and planning. The data collection method is by conducting field surveys, collecting documents related to business processes, interviews and also benchmarking. The method of analysis and planning used is the Enterprise Architecture approach. The results achieved are Producing system strategy planning and technology that is useful for increasing the company's competitive value in future business competition.